Superglue Fuming For The Chemical Enhancement Of Latent Fingerprints - Ahmad, Umi K.; Musa, Afizah (Penerbit UTM Press, 2002)
The acceptance of fingerprint evidence by the courts has always been predicated on the assumption that no two individuals have identical fingerprints. Fingerprints (visible or latent) are often found at a scene of crime. Latent prints however, are difficult to locate and require the utilization of techniques that will visualize the prints. This study involved the application of chemical techniques to the visualization of latent fingerprints. The more recent superglue fuming technique was compared to two other techniques using ninhydrin and eosin as chemical reagents. The chemical enhancement of the three techniques was found to be dependent upon the nature of the surface on which the prints were deposited. Results showed that superglue fuming and eosin technique were capable of enhancing latent fingerprints on non-porous surfaces which have been kept for up to three months. The ninhydrin technique was found to be effective only for latent fingerprints on porous surfaces